2021
DOI: 10.3390/app11083602
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Driven Nitrogen Flow in Divergent Microchannels with Isothermal Walls

Abstract: Gas flow and heat transfer in confined geometries at micro-and nanoscales differ considerably from those at macro-scales, mainly due to nonequilibrium effects such as velocity slip and temperature jump. Nonequilibrium effects increase with a decrease in the characteristic length-scale of the fluid flow or the gas density, leading to the failure of the standard Navier–Stokes–Fourier (NSF) equations in predicting thermal and fluid flow fields. The direct simulation Monte Carlo (DSMC) method is employed in the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…All the solid walls were assumed to be fully diffuse, and heat transfer to the solid porous structure was ignored [ 51 , 52 ]. Detail of the present DSMC model [ 3 , 53 ] and the validity of the results are explained thoroughly in our previous works [ 3 , 12 , 13 , 14 , 19 , 54 ].…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…All the solid walls were assumed to be fully diffuse, and heat transfer to the solid porous structure was ignored [ 51 , 52 ]. Detail of the present DSMC model [ 3 , 53 ] and the validity of the results are explained thoroughly in our previous works [ 3 , 12 , 13 , 14 , 19 , 54 ].…”
Section: Methodsmentioning
confidence: 72%
“…The accuracy of the present DSMC model is also assessed in our previous works by comparing the numerical predictions obtained from the model with experimental and theoretical data [ 3 , 12 , 13 , 14 , 19 , 54 ].…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results verified the ability of DSMC to solve microporous media, and concluded that this method could effectively simulate micro-porous media with porosity of 40%. Ebrahimi et al [94] used the DSMC method to predict the flow and heat transfer characteristics of pressure-driven nitrogen in divergent microchannels, and analyzed the Knudsen number from slip to free molecular rarefaction regimes, as well as studied the effects of microchannel divergence angle, inlet and outlet pressure ratio and sparsity on the thermal field and flow field. Their results found that the effect of the heat flux gradient on the direction of net heat flux increases with the increase of divergence angle.…”
Section: Molecular Dynamic Simulation (Mds) and Direct Simulation Mon...mentioning
confidence: 99%